Dose levotyroxine consumption in hypothyroid patients before dinner change the levels of TSH and T4? - Shahram Ala; Ozra Akha; Zahra Kashi; Hosein Asgarirad; Adeleh Bahar; Neda Sasanpoor (Babol University of Medical Sciences, 2015)
Background: Levothyroxine is commonly used in the treatment of patients with hypothyroidism. Levothyroxine is often administered in the morning, on an empty stomach, to increase its absorption. However, many patients have trouble for taking levothyroxine in the morning. The aim of this study was to evaluate the effect of changing administration time of levothyroxine from before breakfast to before dinner on serum levels of TSH and T4.  Methods: Fifty hypothyroidism patients aged 18-75 years old were included in the study and randomly divided into two groups. Each group received two tablets per day blindly (one levothyroxine tablet and one placebo tablet) before breakfast and before dinner. After two months, the administration time for the tablets was changed for each group, and the new schedule was continued for a further two-month period. The serum TSH and T4 levels were measured before and after treatment in each group.  Results: Changing the levothyroxine administration time, resulted in 1.47±0.51 µIU/mL increase in TSH level (P=0.001) and 0.35±1.05µg/dL decrease in T4 level (P=0.3). Conclusion: Changing the levothyroxine administration time from before breakfast to before dinner minimally reduced the therapeutic efficacy of levothyroxine.